Spatio seasonal variations of water quality and anurans at Maliau Basin, Sabah - Tan, Sin Yee (2017)
Forested watersheds play an important role in supporting aquatic organisms by providing food and habitats. Freshwater organisms inhabit rivers that flow through forested regions and respond to all environmental stresses. Thus, aquatic organisms are useful bioindicators to evaluate and monitor river health and river water quality. Maliau Basin is relatively untouched and lacks scientific documentation. The objectives of this study were to determine spatial variations of physico-chemical water quality parameters, optical parameters, and anurans at Maliau Basin; to evaluate the seasonal variations of physico-chemical water quality parameters, optical parameters and anurans; and to investigate the relationship between physico-chemical water quality parameters, optical parameters and anurans as biological indicators. A total of 12 stations were chosen consisting of four streams representing for different land uses that are altered habitat (AH), main river (MR), secondary forest (SF) and pristine forest (PF) during four sampling occasions (December 2014, March, May and September 2015). Physico-chemical water quality parameters pH, dissolved oxygen, temperature, conductivity, total suspended solids (TSS) and total dissolved solids (TDS) were recorded in-situ. UV-visible absorption coefficients at wavelengths 254nm, 340 nm, and 410nm (a2s4, a340, and a410) and spectral slope were also determined. Anurans were collected at the same stations for water samples via time-constrained opportunistic examination. Discriminant analysis showed that temperature, TSS, and a340 were dominant at AH and MR. For seasonal variations, DO, pH and a340 exhibited differences amongst four occasions. A total of 266 individuals representing 20 anuran species were recorded from the four sampling sites. Low diversity score was observed at AH (H'= 0.861) and MR (H'= 0.818), as compared to forest type habitat (SF and PF) (H' = 1.303 to 1.571). The anuran community showed low seasonal variations ( H' = 1.10 - 1.18). Assessment of the relationships between anurans and water quality parameters was performed using the canonical correspondence analysis. Limnonectes leporinus and Phrynoidis juxtaspera were dominant in high temperature and conductivity, and negatively associated with aromatic/fresher dissolved organic matter content, suggested that these species have the potential to act as biological indicators for disturbed habitats.